Utterly Uncle Fred - Wodehouse, P. G. (Pelham Grenville), 1881-1975 (W. W. Norton & Company, 2012)
Whenever Uncle Fred arrives in London, problems get solved, true lovers are reunited and his nephew Pongo goes into spasms.